Fast non-radiative decay in o-aminophenol - Capello, Marcela Carolina (2014)
The gas phase structure of 2-aminophenol has been investigated using UV-UV as well as IR-UV hole-burning spectroscopy. The presence of a free OH vibration in the IR spectrum rules out the contribution of the cisisomer, which is expected to have an intramolecular H-bond, to the spectra. The excited state lifetimes of different vibronic levels have been measured with pump probe picosecond experiments and are all very short (35 ± 5) ps as compared to other substituted phenols.The electronic states and active vibrational modes of the cisand transisomers have been calculated with ab initiomethods for comparison with the experimental spectra. The Franck Condon simulation of the spectrum using the calculated ground and excited state frequenciesof the transisomeris in good agreement with the experimental one.The very short excited state lifetime of 2-aminophenol can then be explained by the strong coupling between thetwofirst singlet excited states due to the absence of symmetry, the geometry of the transisomer being strongly non planar in the excited state.